Dinamika Sistem Pemerintahan Kesultanan Ternate: Analisis Kritis Integrasi Ino Mano Nako dalam Perspektif Hukum Tata Negara Indonesia - Abdullah, Baharuddin; Ali, Radia; Fikri; Saidah; Muchsin, Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study elaborates on the governance pattern of the Ternate Sultanate as a form of integration between customary law and Islamic law through modern constitutional concepts. This research is significant for enriching the discourse on the diversity of governance systems based on local Indonesian values, which remains limited compared to studies on modern systems. A qualitative method was applied through the study of historical manuscripts, literature, and intensive dialogue with key actors. The findings reveal that this tiered structure represents a harmonious integration of customary law is represented by the Bobato Dunia institution and the Fala Raha council, Islamic law is represented by the Bobato Akhirat institution in the spiritual system, while modern constitutional law concepts are evident in the division of powers and the leader selection mechanism, which reflects an elite democracy. This governance model of the Sultanate demonstrates the adaptation of local values within a modern state system. It also recommends the formal validation of customary governance systems and policies that support regional autonomy without compromising national integration. Further research is required on public perception and comparative studies with other sultanates.